2022
DOI: 10.1093/schbul/sbac155
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Hallucinations and Self-Injurious Behavior in General Population Adolescents: Modeling Within-Person Effects in the Tokyo Teen Cohort

Abstract: Background and Hypotheses A wealth of evidence suggests that adolescent psychotic experiences (PEs), and especially auditory hallucinations (AHs), are associated with an increased risk for self-injurious behavior (SIB). However, the directionality and specificity of this association are not well understood, and there are no published studies investigating within-person effects over time. The present study aimed to test whether AHs and SIB prospectively increase reciprocal risk at the individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Both the CLPM and RI-CLPM models consider covariates. However, incorporating multiple covariates would lead to a more complex model, making it challenging to interpret [ 52 ]. Hence, in this study, we included only non-time-varying control variables, including ACE, education, gender, urban–rural distribution, and regional distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Both the CLPM and RI-CLPM models consider covariates. However, incorporating multiple covariates would lead to a more complex model, making it challenging to interpret [ 52 ]. Hence, in this study, we included only non-time-varying control variables, including ACE, education, gender, urban–rural distribution, and regional distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies of psychosis and suicide in the literature are crosssectional (55)(56)(57), limiting the conclusions that can be drawn to impact the assessment of suicide risk, suicide prevention interventions, and understanding of mechanisms underlying the association between psychosis and suicide risk (55). While many studies have reported that psychosis is a risk factor for suicide (8,10), recent evidence suggests a bidirectional relationship between psychosis-like experiences and suicide thoughts and behaviors (58,59). Further longitudinal studies designed specifically to address these questions of clinical relevance are needed to inform suicide prevention practices.…”
Section: Conduct Longitudinal Observational Studiesmentioning
confidence: 99%
“…Although PLEs have been considered a risk factor for SITBs [10,11], a recent study has proposed a suicidal drive hypothesis, which suggests that SITBs may prompt the emergence of PLEs in some individuals, as a means of externalizing the self-directed threat that arises from SITBs [17]. Three longitudinal studies, utilizing two or three waves of data (collected over 2, 4, 6 years, respectively) have investigated this hypothesis, yielding inconsistent ndings: while two studies supported a temporal association between self-injurious/suicidal behaviors and PLEs/auditory hallucinations [18,19], the other study found no such temporal link [20]. These disparate results may stem from differences in assessments, analytical techniques, and study design/length, as well as confounding factors that have been linked to both phenomena [21].…”
Section: Introductionmentioning
confidence: 99%